Optimization of Pricing and Digital Marketing for Traditional Crafts Buya Sabe and Netu as an Effort to Empower the Economy of Kola-Kola Village, Central Sulawesi Province. - rahmawaty, Santi; Taher, Abdul Rahman (ADPERTISI, 2024)
This research aims to explore pricing strategies and digital marketing in the development of traditional handicrafts Buya Sabe and Netu in Kola-Kola Village. Although these crafts hold significant cultural value and economic potential, the artisans face challenges in setting competitive selling prices and utilizing digital marketing to expand their market. This study uses a qualitative approach with a case study method, where data were collected through in-depth interviews and direct observations of artisans and relevant parties. The results of the research indicate that, before training, the artisans set product prices without calculating the cost of goods sold (COGS), leading to suboptimal profits. After receiving guidance, the artisans began to understand the importance of systematically calculating COGS and adding a reasonable profit margin. Furthermore, the study found that limited access to technology, especially ownership of mobile phones and internet access, is the main obstacle to the implementation of digital marketing. Some artisans who have utilized social media and e-commerce reported an increase in interactions with consumers and orders from outside the region. This study concludes that optimizing pricing strategies and digital marketing can enhance the competitiveness of Buya Sabe and Netu handicrafts. With support from local authorities and collaboration among artisans, the technological access limitations can be overcome, and digital marketing has proven to be effective in expanding market reach. Practical recommendations are provided for artisans in Kola-Kola Village to better optimize their product potential in both local and international markets.